Chlamydial-Secreted Protease Chlamydia High Temperature Requirement Protein A (cHtrA) Degrades Human Cathelicidin LL-37 and Suppresses Its Anti-Chlamydial Activity - Dong, Xiaohua (Med Sci Monit, 2020)
BACKGROUND: Chlamydia trachomatis is an obligate intracellular pathogen that can cause severe reproductive tract complications while ascending infection occurs. When spreading from cell to cell in a host, C. trachomatis utilizes various survival strategies to offset host defense mechanisms. One such strategy is to degrade host antimicrobial defense proteins before they can attack the invading C. trachomatis cells. MATERIAL/METHODS: We expressed and purified recombinant chlamydia high temperature requirement protein A (cHtrA) including 2 cHtrA mutants (MT-H143A and MT-S247A), and also extracted endogenous cHtrA. Proteins were identified and their purity evaluated by SDS-PAGE and Western blot. The anti-chlamydial activity and degradation of 5 antimicrobial peptides (cathelicidin LL-37, α-defensin-1 and -3, and β-defensin-2 and -4) by cHtrA and 2 cHtrA mutants (MT-H143A and MT-S247A) were tested by immunoassay and Western blot. RESULTS: Of the 5 antimicrobial peptides (cathelicidin LL-37, α-defensin-1 and -3, and β-defensin-2 and -4) tested, cathelicidin LL-37 showed the strongest anti-chlamydial activity. Interestingly, cHtrA effectively and specifically degraded LL-37, suppressing its anti-chlamydial activity. The 2 cHtrA mutants (MT-H143A and MT-S247A) were unable to degrade LL-37. Comparison of cHtrA activity from C. trachomatis D, L2, and MoPn strains on LL-37 showed similar responses. CONCLUSIONS: cHtrA may contribute to C. trachomatis pathogenicity by clearing the passage of invasion by specific LL-37 degradation.